CLINICAL, SUBCLINICAL CHARACTERISTICS AND RISK FACTORS OF THE NEW-ONSET DIABETES AFTER TRANSPLANTATION (NODAT) IN LIVING DONOR LIVER TRANSPLANTATION - Quynh, Luu Thuy (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION With the increased number of long-term survivors after liver transplantation, new-onset diabetes after transplantation (NODAT) is becoming more significant in patient followup. However, the incidence of NODAT after living-donor liver transplantation (LDLT) has not been well elucidated. This study aimed to evaluate the incidence, characteristics, and risk factors for NODAT in adult LDLT recipients at a single center in Vietnam. METHODOLOGY This was a retrospective and prospective study of 122 patients who underwent living-donor liver transplantation without pre-transplant diabetes from October 2017 to July 2023 at 108 Military Central Hospital. RESULTS NODAT occurred in 22.9% of liver recipients with a median follow-up time of 19 months. NODAT cases diagnosed within one year after transplantation accounted for 89.2%, with a mean age of 53.96 (10-22 years), and 89.2% of patients were male. BMI >25 kg/m2 accounted for 32.2%. The mean HbA1c in NODAT patients was 6.52 ± 0.78%. There was a negative correlation between NODAT and the patient’s gender, obesity, and family history of diabetes. Other factors, such as hepatitis B and C virus infection, cytomegalovirus infection, the number of HLA antigen disparities between donor and recipient, dialysis, plasma exchange, or pulse steroid were not found to be associated with the incidence of NODAT. Recipient’s age of more than 70 and post-transplant intensive care unit stay >15 days were risk factors for NODAT. CONCLUSION Nearly a quarter of the patients had NODAT. The diagnosis and treatment of NODAT play an important role in the management of patients post-transplantation. More studies are needed to determine the effects of recognition and treatment of hyperglycemia in recent transplant recipients